Triglyceride-glucose index predicts cognitive decline and striatal dopamine deficiency in Parkinson disease in two cohorts - Huimin Cao; Yuying Zhao; Ziyi Chen; Xiaoya Zou; Xinyi Du; Li Yi; Yu Ai; Hongzhou Zuo; Oumei Cheng; Parkinson’s Progression Markers Initiative (npj Parkinson's Disease)
Abstract Heterogeneity is an important feature of cognitive impairment in patients with Parkinson’s disease (PD), with emerging evidence linking insulin resistance to accelerated cognitive decline. Our investigation examined the relationship between the triglyceride-glucose (TyG) index-a marker of insulin resistance-and cognition and striatal dopamine transporter (DAT) alterations in PD through cross-sectional and longitudinal analyses. In the primary cohort, higher TyG correlated with lower Mini-Mental State Examination (MMSE) scores (p < 0.001) and increased dementia risk (p = 0.014). Longitudinal analysis in the PPMI cohort showed higher baseline TyG predicted greater Montreal Cognitive Assessment (MoCA) decline (p = 0.019) and reduced DAT activity in caudate (p = 0.033) and putamen (p = 0.019) over 4 years.DAT activity in the caudate mediated 24.1% of the TyG index’s longitudinal effect on MoCA scores, while the TyG index mediated 16.9% of CSF GLP-1R’s effect. These results highlight the TyG index as a potential biomarker for identifying PD patients at higher risk of cognitive impairment.